Making a Difference for All Kansans 2013 Report to the Legislature - Floros, John D. (My University, 2013)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2013, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN27_2013_01
Keywords: UNN27; Administrative and Research Reports; legislature